Long‐term variations in solar wind velocity and radiation belt electrons. Issue 3 (4th March 2013) - Reeves, Geoff; Morley, Steve; Cunningham, Greg
Abstract : [1] In this paper we analyze the relationship between yearly variations in MeV radiation belt electron fluxes and solar wind velocity (Vsw). We find that the long‐term trends have properties that are important for physical understanding of solar wind‐magnetosphere coupling processes and, potentially, for improvements of short‐term space weather forecasts. A statistical analysis of solar wind velocity shows that years with high average solar wind velocity are not high simply due to a larger number of days with high Vsw. Rather the entire distribution (median and percentiles) shifts along with the mean Vsw. Similar behavior is seen in the MeV geosynchronous electron fluxes. By subtracting out a 365 day running average baseline, we show that the distribution of log fluxes around the mean is remarkably stable from year to year within a solar cycle and from one solar cycle to another. In contrast, the long‐term trends in the baseline show significant changes from year to year and from one solar cycle to another suggesting that solar wind coupling to radiation belt fluxes is not constant but varies over long, as well as short, time scales. In some epicycles, the mean flux is strongly dependent on Vsw while in others the dependence is weak. Similarly, a given average Vsw may produce high average fluxes in one epicycle and low average fluxes in another. Future study of these epicycles and the relative variations within them may improve both physical understanding of solar wind‐magnetosphere coupling and space weather forecasting. Key Points: The radiation belt‐Vsw relationship is not constant over long time scales Distributions of flux and Vsw relative to their means are surprisingly constant Could improve forecasting and understanding of solar wind‐magnetosphere coupling